2007
DOI: 10.1158/1535-7163.mct-06-0794
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of pancreatic tumor growth by combination chemotherapy with sulindac and LC-1 is associated with cyclin D1 inhibitionin vivo

Abstract: The design of novel targeted or combination therapies may improve treatment options for pancreatic cancer. Two targets of recent interest are nuclear factor-KB (NF-KB) and cyclooxygenase (COX), known to be activated or overexpressed, respectively, in pancreatic cancer. We have previously shown that parthenolide, a proapoptotic drug associated with NF-KB inhibition, enhanced the growth suppression of pancreatic cancer cells by the COX inhibitor sulindac in vitro. In the present study, a bioavailable analogue of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
0
27
0
Order By: Relevance
“…30 Subsequently, we also demonstrated that combination chemotherapy with sulindac and DMAPT in vivo suppresses tumor growth in association with cyclin D1 inhibition in BxPC-3 xenograft tumors. 21 In a hamster carcinogen-induced developmental model of pancreatic cancer, DMAPT alone significantly decreases the size of gross pancreatic cancers relative to placebo; the combination of DMAPT/ celecoxib prevents both tumor invasion and metastasis. 20 Despite demonstrating potential chemotherapeutic efficacy, DMAPT and celecoxib, alone or in combination, do not exhibit chemopreventive activity in this carcinogen-induced model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30 Subsequently, we also demonstrated that combination chemotherapy with sulindac and DMAPT in vivo suppresses tumor growth in association with cyclin D1 inhibition in BxPC-3 xenograft tumors. 21 In a hamster carcinogen-induced developmental model of pancreatic cancer, DMAPT alone significantly decreases the size of gross pancreatic cancers relative to placebo; the combination of DMAPT/ celecoxib prevents both tumor invasion and metastasis. 20 Despite demonstrating potential chemotherapeutic efficacy, DMAPT and celecoxib, alone or in combination, do not exhibit chemopreventive activity in this carcinogen-induced model.…”
Section: Discussionmentioning
confidence: 99%
“…The dose of DMAPT chosen for this study was the same as that previously shown to inhibit NF-JB in both xenograft and carcinogeninduced animal models. 20,21 Dimethylaminoparthenolide is currently being evaluated in clinical trials; however, doses of 50 to 100 mg/kg have been used in vivo in canine and mouse models to inhibit NF-JB, without any evidence of toxicity. 34 In the genetically engineered mouse model, we also show that combination DMAPT treatment decreases NF-JB expression in the pancreatic lesions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite widely documented anti-cancer activity and the absence of major adverse effects, clinical development of parthenolide is hampered by its poor water solubility, (35) thus limiting its potential as a promising clinical agent. Previous studies investigated the in vitro and in vivo activities of the water-soluble parthenolide analogue dimethylaminoparthenolide (DMAPT) (20,35,36) and reported that this analogue suppressed tumor growth by targeting NF-κB and generating reactive oxygen (37)(38)(39). The water-soluble parthenolide analogue may become a more readily available radio-sensitizing agent, but further investigation is needed to elucidate its efficacy and spectrum as a radio-sensitizing agent.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have proposed that parthenolide inhibits NF-κB DNA binding activity and function and thereby increases the sensitivity of breast cancer cells to the chemotherapeutic agent Taxol (24). Although the effect of parthenolide as an inhibitor of NF-κB activity has been reported previously in several cancer cell lines (22,23,25,26), its significance, detailed mechanism, potential use in treatment, and adjuvant approach in combination with Taxol chemotherapy has not yet fully been investigated in human non-small cell lung cancer (NSCLC).…”
Section: Introductionmentioning
confidence: 99%